2019
DOI: 10.1371/journal.pone.0215500
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices related to hypertension among residents of a disadvantaged rural community in southern Zimbabwe

Abstract: Background Hypertension contributes significantly to cardiovascular and renal diseases. It can be controlled by lifestyle modifications, however in poor communities there is lack of awareness, and treatment and control of hypertension is often poor. The aim of this study was to determine hypertension knowledge, attitudes and practices in a disadvantaged rural community in Matebeleland South province of Zimbabwe. Methods We conducted a descriptive cross-sectional survey … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 20 publications
6
55
2
Order By: Relevance
“…Knowledge related to hypertension was poor. The educational status of respondents was an independent predictor of knowledge about hypertension [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge related to hypertension was poor. The educational status of respondents was an independent predictor of knowledge about hypertension [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Cameroon, although moderate to high knowledge levels on CVD risk factors were reported, overall knowledge scores were equally low and gaps in warning signs for heart attack and stroke were found [ 20 ]. Moreover, studies have shown that even with the high prevalence of CVD risk factors such as hypertension in many SSA countries, awareness and control remains low [ 6 , 21 , 22 ] amidst low population knowledge [ 13 , 23 ] affecting health care seeking, diagnosis and treatment. It is therefore imperative that interventions to improve population knowledge about CVD and its risk factors such as those premised on health promotion and awareness raising are implemented to contribute to prevention and control efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, their inability to understand, receive and utilize health management techniques. In a related study, [39] reiterated the role of education and that respondents with more education may more likely be aware and knowledgeable about the utilization of hypertension management techniques as this is an important aspect of any programs and interventions designed to control rate of hypertension in the study area.…”
Section: Level Of Educationalmentioning
confidence: 99%